Orexin-A Attenuates Inflammatory Responses in Lipopolysaccharide-Induced Neural Stem Cells by Regulating NF-KB and Phosphorylation of MAPK/P38/Erk Pathways - Ye W; Yan Y; Tang Y; Dong X; Chen G; Kang J; Huang L; Xiong Q; Feng Z (Dove Medical Press, 2021)
Wen Ye,1 Yan Yan,2 Yunliang Tang,1 Xiaoyang Dong,1 Gengfa Chen,1 Junwei Kang,1 Lianghua Huang,1 Qi Xiong,1 Zhen Feng1 1Department of Rehabilitation, The First Affiliated Hospital of Nanchang University, Nanchang City, Jiangxi Province, People’s Republic of China; 2Department of Nephrology, The First Affiliated Hospital of Nanchang University, Nanchang City, Jiangxi Province, People’s Republic of ChinaCorrespondence: Zhen FengDepartment of Rehabilitation, The First Affiliated Hospital of Nanchang University, Nanchang City, Jiangxi Province, People’s Republic of ChinaEmail medstu@126.comBackground: Neuronal damage is the main cause of neurological diseases. Neural stem cells (NSCs) have the functions of cell repair and replacement of neurons, secretion of neurotrophic factors, and immune regulation of the neural microenvironment.Objective: Previous study found that Orexin-A had a protective effect on neurons in the central nervous system, but it is lacking in making great efforts on the function of Orexin-A on NSCs. This study aimed to investigate the anti-inflammatory responses and signaling mechanisms of Orexin-A on lipopolysaccharide (LPS)-induced NSCs.Methods: Quantitative real-time polymerase chain reaction was used to detect the mRNA level. Signaling pathway-related protein expression was detected by Western blot. The proliferation and migration of NSCs were investigated by Cell Counting Kit-8 (CCK-8) detection kit and transwell assay. Besides, the staining of hematoxylin and eosin (HE) was performed to study the morphology of cell.Results: Orexin-A decreased the pro-inflammatory cytokines of IL-1β, TNF-α, and IL-6 induced by LPS by regulating nuclear factor-k-gene binding (NF-kB) and phosphorylation of P38/Erk-mitogen-activated protein kinases (MAPKs) pathways, but not p-JNK signaling.Conclusion: Our findings indicate that Orexin-A can alleviate the inflammatory response of NSC. It can provide beneficial help in neural stem cell therapy applications.Keywords: NSCs, Orexin-A, NF-kB, MAPK